A New High Performance MPPT Method using Only DC-DC Converter in Partial Shade Conditions - Parlak, Koray Sener (Univ Suceava, Fac Electrical Eng, 2023)
photovoltaic (PV) has become one of the most important renewable energy sources today. Getting the maximum power from these systems in changing environmental conditions is an important research subject. Maximum power point trackers (MPPT) are used to get the highest efficiency from PV arrays under current irradiance and temperature conditions. Additional hardware such as sensors, partial shading, and complex algorithms are factors affecting MPPT performance. The MPPT method proposed in this study does not require any additional hardware, has a simple algorithm, is easy to implement and can extract maximum power from the PV array even under partial shading conditions. In the proposed method, firstly, the electrical characteristic of the PV array is obtained by emulating the dc-dc converter as a load. The maximum power point of the array was found using the current and voltage data during this process. Subsequently, the PV array was operated at this point and the maximum power was harvested. The proposed method was validated on the Matlab-Simulink environment by simulating various irradiance values.
Keywords: Index Terms-photovoltaic arrays; maximum power point tracker; partial shade conditions; solar systems; maximum power